The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1021/jf950752q
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Characterization of Spring Spelt Wheat Gliadins

Abstract: Gliadin compositions of 95 spring spelts, 5 winter spelts, and Neepawa Hard Red Spring (HRS) wheat were evaluated by acid−polyacrylamide gel electrophoresis (A-PAGE). Five spring spelts grown in three environments over 2 years were compared to the HRS cultivar Katepwa using A-PAGE and sodium dodecyl sulfate−polyacrylamide gel electrophoresis (SDS-PAGE). On the basis of the scoring of 13 bands, the spring and winter spelts diverged widely from Neepawa HRS wheat. None of the spring spelts evaluated had a gliadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
4
14
0
Order By: Relevance
“…The similar electrophoretic characterisation of spelt seed gliadins was studied by several authors (Abdel-Aal et al 1996, Harsch et al 1997, aek and Èerný 1997. HMW glutenin subunits may be used as a molecular marker of bread-making quality of wheat.…”
Section: Resultsmentioning
confidence: 79%
“…The similar electrophoretic characterisation of spelt seed gliadins was studied by several authors (Abdel-Aal et al 1996, Harsch et al 1997, aek and Èerný 1997. HMW glutenin subunits may be used as a molecular marker of bread-making quality of wheat.…”
Section: Resultsmentioning
confidence: 79%
“…The reality of the mutual LMW-glutenins and gliadins overlapping or the ability of HMW-glutenin fraction passes to the gliadin fraction in conditions of SDS-PAGE was published very often (Pomeranz et al 1988, Abdel-Aal et al 1996, Ovesná et al 2001 and from this viewpoint it is also possible to register a historical development. Miflin et al (1983) recommended that all wheat endosperm proteins should be called gliadins, while Field et al (1982) named the two major storage protein groups aggregative gliadins (glutenins) and non-aggregative gliadins.…”
Section: Entire Evaluationmentioning
confidence: 99%
“…Canadian authors found the basic differentiating regions of spelt gliadins, in which the heaviest group of omega gliadins (100-113 kDa) and higher number of alpha gliadin bands are absent in comparison with common wheat (Abdel-Aal et al 1996). German authors constructed ideal spelt gliadin pattern, where the heaviest group of omega gliadins was also absent, in comparison with common wheat, and additionally on the basis of A-PAGE analyses they described a new D-zone of bands, located between omega and gamma gliadins.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It has been well documented that glutenins have major effects on bread-making quality due to their contributions to dough strength (Payne, 1987). In addition, storage proteins are also reliable genetic markers for investigating genetic diversity in wheat (Branlard et al, 2001;Abdel-Aal et al, 1996), marker-assisted selection (Ahmad, 2000) and wheat origin and evolution (Yan et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%